CEPUNG SASAK: ORAL TRADITION IN LOMBOK WEST NUSA TENGGARA - Kade Gunayasa, Ida Bagus; Weda Kusuma, I Nyoman; Cika, I Wayan; Suarka2, I Nyoman (e-Journal of Linguistics; Vol. 5. Januari 2011 No. 2, 2011)
The problems discussed in this study are the process of the creation of CepungSasak (abbreviated to CS), its structure, its context of image, its function and meaning.The data needed was collected by ethnographic method and library research. Four maintheories were adopted for analyzing the data; they are the structural theory, the Lord’sformula, the theory of literary semiotics and the functional theory. The objectives wereachieved by analyzing the process of the CS creation, its textual structure, its context ofimage, its function and meaning in the middle of Sasaknese community.Based on the results of the data analysis, it can be inferred that the elementsforming the CS structure are form, formula, theme, sound and style. One of the culturalcontextual elements which does not play any role is the particular event underlying theimage. The process of its creation takes place within and outside the plots. Its plotsfunction to recall the past, to educate, to amuse, to express interethnic group solidarity, tocontrol social matters, to resist social matters and to give religious teachings. Themeanings of the CS are love and affection, acknowledgement of social stratification andcollective awareness.The novelties in this study are the formula and theme are different from thoseintroduced in the Lord’ theory. The Lord’s theory of formula is not entirely applicable tothe CS. The reason is that the process how the CS is created is not based on formula buton the pattern of rhyme and stimulus such as flute, rebab (two-stringed musicalinstrument), music produced by the mouth and pengeriong ‘penurut’ (another musical instrument). The process of how it is created is not the same as that stated by Lord. It issimilar to that stated by Finnegan, that is, it takes place within and outside the plots.However, Finnegan does not include the element of stimulus. In this case, the mainfunction of the CS is as amusement. Its meaning is to stimulate social solidarity in allaspects of Sasaknese community life.
Keywords: Cepung Sasak; collectivity; spontaneity; fetishism; contextual